O espaço central das atenções: o corredor de integração da Região Metropolitana de Natal - Silva Júnior, José Petronilo da (2007)
This work considers the space study of the main road runner of integration of the Region Metropolitan of Natal (RMN) in formation, emphasizing its repercussion for the geographic context of the city, where we identify the positive and negative aspects of such space configuration, as for the aspects of the urban inaquality, economic centrality and of flows, promoted for the state and private capital (national and foreign). The linear convergence and polinucleately of geographic objects in that we identify as Central Space of Attentions (CSA), promoted, and still it promotes, important repercussion in the space estructuretion of the peripheral areas of the RMN, such as in the constitution of the "Capital Value of the Space". In this direction, to endorse the analysis of such reading, choose as cientific ballast the geographic theory, in a perspective dialectic, as well as we rescue contributions of the science of the administration, sociology, economy, amongst others. From the empirical research, subsidized with the application of forms together the entrepreneurs whom they possess investments in the CSA, as well as in the rescue of information you register in cadastre in the Junta Comercial do Estado do Rio Grande do Norte (JUNCERN) and telephonic list, we construct a proposal of reading of the current period of training of the process of space production to which is rank the CSA. The analysis of the data, under a comparative space angle, presents an important contribution to reevaluate the urban space of the RMN in its bigger aspect, exceeding the limits of the studied road corridor